2008
DOI: 10.1111/j.1399-3038.2007.00692.x
|View full text |Cite
|
Sign up to set email alerts
|

Serum levels of Th2 chemokines, CCL17, CCL22, and CCL27, were the important markers of severity in infantile atopic dermatitis

Abstract: Atopic dermatitis (AD) is considered to be Th2 cell-mediated disorder. In most infants with AD, AD may be induced by food allergy. In the early stage of infantile AD, it is unclear whether there are changes in serum Th2 chemokines or in Th2 chemokine production by peripheral blood mononuclear cells (PBMC). Thirty-four patients with AD were examined (mean age, 4.5 months; female:male, 18:16). Ten age-matched infants with no history of allergic disease were used as controls. Thirty of these 34 patients were sens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
85
0
7

Year Published

2008
2008
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(102 citation statements)
references
References 24 publications
8
85
0
7
Order By: Relevance
“…Elevated serum levels of the IL-4-and IL-13-induced chemokines CCL11, CCL17, CCL18, and CCL22 (9 -12) have previously been associated with allergic manifestations, in particular AD (13)(14)(15). The amplification of the allergic response is partly driven by CCL17 and CCL22 because they attract CCR4 receptor expressing Th2 lymphocytes, mast cells, dendritic cells, and natural killer T (NKT) lymphocytes to the site of inflammation (16).…”
mentioning
confidence: 99%
“…Elevated serum levels of the IL-4-and IL-13-induced chemokines CCL11, CCL17, CCL18, and CCL22 (9 -12) have previously been associated with allergic manifestations, in particular AD (13)(14)(15). The amplification of the allergic response is partly driven by CCL17 and CCL22 because they attract CCR4 receptor expressing Th2 lymphocytes, mast cells, dendritic cells, and natural killer T (NKT) lymphocytes to the site of inflammation (16).…”
mentioning
confidence: 99%
“…CCL22 levels were significantly elevated and were correlated with the severity of disease in atopic patients (Nakazato et al, 2008). The imbalance in serum CCL22 concentrations contributes to AD development (Narbutt et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Leung et al, 2003;Mostafa et al, 2008;Nagy et al, 2011;Song et al, 2006;Sohn et al, 2004;Kakinuma et al, 2002Kakinuma et al, ,2008Jahnz-Rozyk et al, 2005;Hijnen et al, 2004;Kakinuma et al, 2001). Among the Th2 chemokines, serum CCL27 correlated most significantly with the severity of AD (Nakazato et al, 2008).The research by Miyahara et al showed that increased level of CCL17 in umbilical cord serum of neonates destined to develop AD in infancy (Miyahara et al, 2011).But another research indicated that the serum level of CCL17 and IL-18 were decreased, and CXCL12 and CCL27 increased in kids younger than 10 years old. In childhood AD of over 10 years old, serum concentration of CXCL12, CCL17, CCL22 was higher (Toda et al, 2003).There are many research results confirmed that the increased CCL28 level in the serum of AD patients and correlated positively to the severity scores (Jahnz-Rozyk et al, 2005; T.F.…”
Section: Interleukinsmentioning
confidence: 99%